2017
DOI: 10.1108/dat-06-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness among clients of Sydney’s supervised injecting facility

Abstract: Purpose The Uniting Medically Supervised Injecting Centre (MSIC) opened in Sydney, Australia, in May 2001. Homelessness among people who inject drugs (PWID) in Australia has been increasing, and establishing how supervised injecting facilities (SIFs) might best support clients into housing is an important goal. The purpose of this paper is to update knowledge regarding the accommodation status of MSIC clients, thereby supporting a better understanding of the complex needs of these clients. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Research from different international settings has consistently shown that more marginalized people use SIFs [5]. Despite different settings [5], frequent SIF attendance increased the likelihood of referral to health and social services [11,13] and engagement in drug treatment [31,32]. However, we found that such indicators of SIF service use were weaker determinants for requesting support than variables indicative of marginalization (i.e., homelessness, heroin use), self-identified needs and existing contact with relevant services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research from different international settings has consistently shown that more marginalized people use SIFs [5]. Despite different settings [5], frequent SIF attendance increased the likelihood of referral to health and social services [11,13] and engagement in drug treatment [31,32]. However, we found that such indicators of SIF service use were weaker determinants for requesting support than variables indicative of marginalization (i.e., homelessness, heroin use), self-identified needs and existing contact with relevant services.…”
Section: Discussionmentioning
confidence: 99%
“…Uniting’s Sydney Medically Supervised Injecting Centre (referred to as Sydney SIF herein) is the first and longest-running supervised injecting facility in the Southern Hemisphere, and over 16,000 clients have registered with the service since 2001. Sydney SIF clients manifest high levels of marginalization and unstable housing [13]. Overall, there are indications that the population of people who inject drugs (PWID) is aging in Australia [14,15] and elsewhere [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 This is consistent with studies that have shown, over shorter durations, a positive relationship between SIF utilisation and likelihood of referral to health and social services. [47][48][49][50] Shorter term studies from Vancouver's Insite have reported a large volume of referrals made in a 12month period, with a substantial proportion (40%) for addiction treatment 51 and a concurrent 30% increase in the uptake of detoxification services. 52 Kennedy et al 38 found that SIFs can play a role in the cessation of injecting drug use through referrals into treatment.…”
mentioning
confidence: 99%